Impact of Battery Degradation on Thermal Runaway Risks in Lithium-ion Batteries: a Statistical and Modelling Approach - Milad Tulabi; Roberto Bubbico (Chemical Engineering Transactions)
Li-ion batteries are commonly used in an increasing number of applications, but they are characterized by different safety problems connected with their operating temperature. In fact, depending on the balance between the heat internally produced during operation and that dissipated towards the external environment, a thermal runaway can occur beyond certain values of the internal temperature, with possible dangerous events, such as fires and explosions. While most existing research investigates TR in new or minimally cycled batteries, real-world TR incidents predominantly occur in aged batteries, underscoring the need for a targeted investigation into the aging effects. This study will examine the effect of battery degradation on the likelihood of thermal runaway (TR) events, with a focus on the main degradation parameters that impact thermal behavior in lithium-ion batteries (LIBs), such as internal resistance, the charge/discharge current, and the cell capacity. A mathematical model was developed and validated against established literature, allowing for a detailed statistical analysis of each parameter's influence on TR. Preliminary results indicate that charge/discharge current is the most significant contributor, showing the lowest p-value with confident level of 95% in relation to temperature increases at a state of charge (SOC) of 50%. The findings of this study will enhance understanding of TR risks in aged LIBs and provide a foundation for improved battery management strategies to mitigate safety hazards in degraded batteries.